HSV-NIS, an oncolytic herpes simplex virus type 1 encoding human sodium iodide symporter for preclinical prostate cancer radiovirotherapy - Li, H (Nature Publishing Group, 2013)
Several clinical trials have shown that oncolytic herpes simplex virus type 1 (oHSV-1) can be safely administered to patients. However, virus replication in tumor tissue has generally not been monitored in these oHSV clinical trials, and the data suggest that its oncolytic potency needs to be improved. To facilitate noninvasive monitoring of the in vivo spread of an oHSV and to increase its antitumor efficacy, the gene coding for human sodium iodide symporter (NIS) was incorporated into a recombinant oHSV genome and the corresponding virus (oHSV-NIS) rescued in our laboratory. Our data demonstrate that a human prostate cancer cell line, LNCap, efficiently concentrates radioactive iodine after the cells have been infected in vitro or in vivo. In vivo replication of oHSV-NIS in tumors was noninvasively monitored by computed tomography/single-photon emission computed tomography imaging of the biodistribution of pertechnetate and was confirmed. LNCap xenografts in nude mice were eradicated by intratumoral administration of oHSV-NIS. Systemic administration of oHSV-NIS prolonged the survival of tumor-bearing mice, and the therapeutic effect was further enhanced by administration of (131)I after the intratumoral spread of the virus had peaked. oHSV-NIS has the potential to substantially enhance the outcomes of standard therapy for patients with prostate cancer.